Islamic Religious Learning in Religious Tolerance in Preschool - Anwar Zain; Muhammad Zulkarnaen; Muhammad yusuf (Tajdid Al-Athfal, 2023)
School TK. Widya Dharma have student various religions, namely Islam, Christianity, Catholicism and Buddha . School this in development emphasized religious aspects in 2 ( two ) dimensions religious , that is first child age early very important introduced about religion for children internalized deep religious values worship. Second , child implanted nature tolerance religion ever since early so that the child already used to with attitude tolerance fellow her friend although different religion. Therefore, researchers conducted research namely: How is the implementation of religious learning? . The research uses a qualitative method of field research approach (field research) with interview techniques, observation and documentation. The subjects in this study were Islamic religious teachers. While the object of this research is the implementation of religious learning The results of the research are that the implementation of religious learning in this school is given exclusively according to the religion of each child once a week, including; faith, prayer/way of worship, prayers, reading and understanding religious scriptures, religious songs or hymns, introducing fasting and introducing the days of worship or religious anniversaries of each. The way to implement the planting of religious tolerance is through several activities including introducing the nature of religious tolerance and enabling children to experience the benefits of religious tolerance.